2021
DOI: 10.1029/2020jd033799
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Aerosol‐Droplet Partitioning on Turbulence in a Laboratory Cloud

Abstract: Activation is the first step in aerosol‐cloud interactions, which have been identified as one of the principal uncertainties in Earth's climate system. Aerosol particles become cloud droplets, or activate, when the ambient saturation ratio exceeds a threshold, which depends on the particle's size and hygroscopicity. In the traditional formulation of the process, only average, uniform saturation ratios are considered. However, turbulent environments like clouds intrinsically have fluctuations around mean values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…If the dynamics of evaporation are neglected and, instead, droplets are assumed to reach equilibrium with the environment instantaneously, particles in regions with s ≥ s crit would be activated, whereas particles in regions with s < s crit would not be activate. This was the assumption applied in Shawon et al (2021) and Prabhakaran et al (2020). However, in a real cloud, droplets do not respond instantaneously to fluctuations in s, which leads to further enhancements in CCN activation, shown by the difference between dashed and solid green lines in Figure 2c.…”
Section: Elevated Ccn Activity Due To Evaporation Dynamicsmentioning
confidence: 96%
See 1 more Smart Citation
“…If the dynamics of evaporation are neglected and, instead, droplets are assumed to reach equilibrium with the environment instantaneously, particles in regions with s ≥ s crit would be activated, whereas particles in regions with s < s crit would not be activate. This was the assumption applied in Shawon et al (2021) and Prabhakaran et al (2020). However, in a real cloud, droplets do not respond instantaneously to fluctuations in s, which leads to further enhancements in CCN activation, shown by the difference between dashed and solid green lines in Figure 2c.…”
Section: Elevated Ccn Activity Due To Evaporation Dynamicsmentioning
confidence: 96%
“…Mixing of air parcels within a cloud is one of the causes of fluctuations in the water vapor mixing ratio and temperature, leading to fluctuations in water vapor supersaturation, s (Anderson et al., 2021; Gerber, 1991; Korolev & Isaac, 2000; Kulmala et al., 1997; Siebert & Shaw, 2017). Despite a number of studies proposing that small‐scale fluctuations in s due to turbulent mixing impact cloud droplet formation and the cloud droplet size distribution (Abade et al., 2018; Chandrakar et al., 2016; Grabowski & Abade, 2017; Grabowski et al., 2022a, 2022b; Hoffmann et al., 2019; MacMillan et al., 2022; Prabhakaran et al., 2020; Saito et al., 2019; Shawon et al., 2021; Siewert et al., 2017), the impact of these fluctuations on cloud condensation nuclei (CCN) activity has not been well quantified and is often neglected in large‐scale atmospheric models.…”
Section: Introductionmentioning
confidence: 99%
“…For the same temperature difference, the atmospheric length scales are 1,000 times that of the cloud chamber. Hence, it is necessary to scale the results of aerosol‐cloud‐turbulence interactions (Bhandari et al., 2019; Chandrakar et al., 2018; Prabhakaran et al., 2020; Shawon et al., 2021) from cloud chamber to the atmosphere. To be clear, the goal in the laboratory is not to match Ra and Re in the atmosphere, which is likely impossible, but rather to explore atmospherically‐relevant ranges of microphysical dimensionless numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus for the Pi Chamber with a fixed geometry, and a selected convecting fluid, only about 2 orders of magnitude of Rayleigh numbers (i.e., 10 8 –10 10 ) can be explored (Chang et al., 2016). Furthermore, decoupling the Rayleigh number from the thermodynamic forcing requires altering the water vapor boundary conditions, for example, by using salt solutions (Shawon et al., 2021). In practice the Rayleigh number ranges explored have been limited to about 1 order of magnitude due to experimental limitations (Niedermeier et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, supersaturation fluctuations are expected to be larger at the cloud edge, while the mean supersaturation is larger at the cloud core. Supersaturation fluctuation's effect on activation has been investigated recently (Abade et al., 2018; Grabowski et al., 2022; Prabhakaran et al., 2020; Shawon et al., 2021). It was found that, under the influence of strong supersaturation fluctuation, the drop size distribution is broadened (Abade et al., 2018; Grabowski et al., 2022; Tölle & Krueger, 2014) and a large fraction of particles remain unactivated (Prabhakaran et al., 2020).…”
Section: Introductionmentioning
confidence: 99%